Magnitude and determinants of behavioral risk factors of non-communicable diseases among reproductive age women in Gofa and Basketo zones, Southern Ethiopia: a community-based cross-sectional study - Domba, Markos Manote; Argefa, Terefe Gelibo; Kebede, Bahiru Mulatu; Sako, Sewunet (Frontiers in Public Health, 2025)
BackgroundAs of 2019, around 2 billion reproductive-age women worldwide were impacted by NCDs and their associated risk factors. The purpose of this study is to investigate the magnitude and factors associated with behavioral risk factors among reproductive-age women in the Gofa and Basketo zones of Southern Ethiopia, with the goal of improving care options for women with NCDs before, during, and after pregnancy.MethodsA community-based survey was conducted using instruments adapted and developed from the WHO STEPS surveillance manual and various literatures on chronic disease risk factors. A multistage cluster sampling approach was employed to select individuals from the two zones. Statistical analysis was performed using the Statistical Package for the Social Sciences (SPSS) software. Descriptive statistics, bivariate analysis, and multivariate logistic regression were conducted. Associations with a p ≤ 0.05 were considered statistically significant.ResultsApproximately 90.9% (95% CI: 89.9–90.2) of participants exhibited one or more behavioral risk factors. High dietary salt intake was the most common risk factor accounting for 90.0%. Statistically significant associations with the co-occurrence of behavioral risk factors were found among women in younger age groups, rural residents, Gofa zone residents, widowed/divorced or single individuals, merchants, housewives, individuals from households with a lower wealth index, those with lower educational attainment, and having a family history of NCDs. Conversely, being a government employee, mass media user, having good knowledge of NCD risk factors, having social support, and being a member of the functional Women Development Army (WDA) were identified as protective factors.ConclusionThe escalation of behavioral risk factors is concerning, highlighting the urgent need for targeted community-based interventions. It is recommended to prioritize younger age groups, rural residents, those with lower wealth status, and lower educational attainment. Implementing family-oriented changes and strengthening healthcare systems are crucial. Additionally, addressing policy and socio-political factors influencing the rise of NCD risk factors is essential.